2020
DOI: 10.1055/s-0039-3402762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tranexamic Acid on Coagulation and Fibrin Clot Properties in Children Undergoing Craniofacial Surgery

Abstract: Objective Craniosynostosis surgery in small children is very often associated with a high blood loss. Tranexamic acid (TXA) reduces blood loss during this procedure, although the potential underlying coagulopathy in these children is not known in detail. Objective was to determine the nature of any coagulopathy found during and after craniosynostosis surgery and to characterize the effect of TXA on fibrin clot formation, clot strength, and fibrinolysis. Materials and Methods Thirty children received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Endogenous thrombin potential in mice that received emicizumab only was 363±130 nm.min (mean±SD) and 363±95 nm.min in those treated with emicizumab+TxAc ( P > .05, Mann Whitney U test). In accordance with previous clinical studies, the suppression of fibrinolytic activity by TxAc has no additional procoagulant effect on thrombin generation capacity 13,14 . We previously showed that thromboelastography was very sensitive to the TxAc effect; curves and thromboelastography parameters could be fully normalized with TxAc alone without any contribution from exogenous factor VIII 2 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Endogenous thrombin potential in mice that received emicizumab only was 363±130 nm.min (mean±SD) and 363±95 nm.min in those treated with emicizumab+TxAc ( P > .05, Mann Whitney U test). In accordance with previous clinical studies, the suppression of fibrinolytic activity by TxAc has no additional procoagulant effect on thrombin generation capacity 13,14 . We previously showed that thromboelastography was very sensitive to the TxAc effect; curves and thromboelastography parameters could be fully normalized with TxAc alone without any contribution from exogenous factor VIII 2 .…”
Section: Resultssupporting
confidence: 89%
“…In accordance with previous clinical studies, the suppression of fibrinolytic activity by TxAc has no additional procoagulant effect on thrombin generation capacity. 13,14 We previously showed that thromboelastography was very sensitive to the TxAc effect; curves and thromboelastography parameters could be fully normalized with TxAc alone without any contribution from exogenous factor VIII. 2 However, this observation is inconsistent with clinical experience where TxAc alone is not usually sufficient to control bleeding in patients with severe haemophilia A.…”
Section: Resultsmentioning
confidence: 99%
“…Of the reviewed studies, fifteen assessed the use of TXA in craniofacial surgery procedures [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Of these, nine were retrospective cohort studies [29-31, 34, 35, 38-40, 42], and six were randomized controlled clinical trials [32,33,36,37,41,43]. Study sample ranged from 25 to 187 patients, apart from a single retrospective cohort study of 1638 patients.…”
Section: Craniofacial Surgerymentioning
confidence: 99%
“…Eight studies reported a notable decline in transfusion requirements, owing to decreased intraoperative bleeding, ranging from 19 to 85% [28,[31][32][33][34][37][38][39]. Other notable outcomes included a clearer surgical field [36], shorter length of hospital stay [40], lower drop in postoperative hemoglobin level, higher postoperative estimated red cell volume [30], and decreased surgical drain Fig.…”
Section: Craniofacial Surgerymentioning
confidence: 99%
“…TXA is a synthetic lysine analog that binds reversibly to lysine receptor sites on plasminogen. This step reduces conversion of plasminogen to plasmin whereby the level of plasmin drops significantly and prevents fibrin degradation and supports preservation of the fibrin network 3,4 . Both plasminogen and plasmin play pivotal role as inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%